2022
DOI: 10.3389/fonc.2022.937277
|View full text |Cite
|
Sign up to set email alerts
|

CT-based radiomics in predicting pathological response in non-small cell lung cancer patients receiving neoadjuvant immunotherapy

Abstract: ObjectivesIn radiomics, high-throughput algorithms extract objective quantitative features from medical images. In this study, we evaluated CT-based radiomics features, clinical features, in-depth learning features, and a combination of features for predicting a good pathological response (GPR) in non-small cell lung cancer (NSCLC) patients receiving immunotherapy-based neoadjuvant therapy (NAT).Materials and methodsWe reviewed 62 patients with NSCLC who received surgery after immunotherapy-based NAT and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…They concluded that the radiomics and deep learning models were wellperforming and predictable tools for malignancy of solid pulmonary nodules [34] . Lin et al showed that a jointly constructed model with all clinical, conventional radiomic, and deep learning features had a great accuracy for predicting a good pathological response (GPR) in non-small cell lung cancer (NSCLC) patients receiving immunotherapy-based neoadjuvant therapy (NAT) [35] . Our novel approach makes analyzing the inherent connections between variables and outcomes easier, thereby improving the model's accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the radiomics and deep learning models were wellperforming and predictable tools for malignancy of solid pulmonary nodules [34] . Lin et al showed that a jointly constructed model with all clinical, conventional radiomic, and deep learning features had a great accuracy for predicting a good pathological response (GPR) in non-small cell lung cancer (NSCLC) patients receiving immunotherapy-based neoadjuvant therapy (NAT) [35] . Our novel approach makes analyzing the inherent connections between variables and outcomes easier, thereby improving the model's accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on contrast-enhanced CT before neoadjuvant immunotherapy, a study used radiomic features, clinicopathological information, and DL features to construct a model for the prediction of a good pathological response, finding an AUC of 0.805 [ 82 ]. In another study, a combination of radiomics and DL was used for predicting the response of NSCLC patients with advanced disease to immunotherapy with an AUC of 0.960 [ 83 ].…”
Section: The Application Of Ai In Predicting the Response To Immunoth...mentioning
confidence: 99%
“…Yoo et al constructed a highperformance ML model with AUC over 0.97 from 18 F-FDG PET-CT radiomics features to predict pCR after neoadjuvant chemoimmunotherapy in NSCLC (101). The accuracy of the prediction using the ML model was significantly higher than that derived using conventional image features (101,102).…”
Section: Machine Learningmentioning
confidence: 99%